Implementation of occupational safety and health targets to reduce risks in nursing procedures - Lana Yusria (Safety and Health for Medical Workers, 2024)
Background: Ensuring occupational safety and health in nursing procedures is essential to mitigate risks for both nurses and patients. Adhering to protocols and implementing patient safety targets are crucial for error prevention.Method: This descriptive study correlates occupational safety measures with error reduction in nursing procedures. Patient safety targets are analyzed for their impact on nurse performance and patient outcomes.Result Innovation: Implementation of six patient safety targets enhances nurse adherence to procedures, reducing errors and promoting patient safety. Effective communication and oversight of medication administration are highlighted as key factors.Conclusion: Prioritizing nurse safety through occupational safety measures improves patient care quality by minimizing errors. Professionalism and positive attitudes among nurses contribute significantly to error prevention and overall safety.Implications and Theory: Effective implementation of occupational safety measures not only safeguards nurses' well-being but also enhances patient care outcomes. The findings underscore the importance of proactive safety measures and positive attitudes in nursing practice.